A Monte Carlo Study of a Factor Analytical Method for Fixed-Effects Dynamic Panel Models - Milda Norkute (Lund University, School of Economics and Management, Department of Economics, 2014)
In a recent article Bai (Fixed-Effects Dynamic Panel Models, A Factor Analytical Method. Econometrica 81, 285-314, 2013a) proposes a new factor analytical method (FAM) for the estimation of fixed-effects dynamic panel data models, which has the unique and very useful property that it is asymptotically bias free. In this paper we provide Monte Carlo evidence of the good small-sample performance of FAM, that complement Bai's theoretical study.
Keywords: C13; C33; 330; Dynamic panel data models; Heteroscedasticity; Monte Carlo simulations